Quantum Information from Graviton-Matter Gas - Glinka, Lukasz-Andrzej (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We present basics of conceptually new-type way for explaining of the origin, evolution and current physical properties of our Universe from the graviton-matter gas viewpoint. Quantization method for the Friedmann-Lemaitre Universe based on the canonical Hamilton equations of motion is proposed and quantum information theory way to physics of the Universe is showed. The current contribution from the graviton-matter gas temperature in quintessence approximation is discussed.